Ketahanan Pangan Berbasis Sumberdaya Lokal : Konsumsi Pangan dan Status Gizi pada Penduduk Asli di Wilayah Bantaran Sungai dan Non Bantaran Sungai, Kalimantan Timur - Ahmad Suhaimi (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2012)
The research aimed to examine food consumption and nutritional status in the household of indigenous people “Dayak” which resided at the low line of Mahakam river, and to conduct the study on social, culture, and economic factors which affected the food consumption. The research result showed average energy and protein consumption per person was 2.000,7 kcal and 71,0 gram which the actual energy consumption level was 100,04 % and actual protein consumption level was 136,5 %. The value of actual energy consumption level was in the good category ((>100% of RDA) and actual protein consumption level was in the good category (>100% of RDA). When the nutritional status of children under five was related to energy consumption level of household, the prevalence of malnutrition was in the low and deficit category for energy consumption level of household; and the good nutritional status tended to be in the sufficient and good category for energy consumption level of household. The estimation was also supported by the Pearson Correlation of p=0.0001 and r=0.692. It could be understood their was highly significant relationship of nutritional status of children under five and the energy consumption level of household. The socio-culture, economic factors which affected food consumption of household were : nutritional awareness of mother (p=0.016), food preference (p=0.023), food avoidance (p=0.000), inequality of member in the household (p=0.000), and income level of household (p=0.001)